1998
DOI: 10.1046/j.1432-1327.1998.2520400.x
|View full text |Cite
|
Sign up to set email alerts
|

Galectin‐1 from ovine placenta

Abstract: In the present study we report the amino-acid sequence, carbohydrate specificity and overall biochemical and physicochemical properties of galectin-1, a β-galactoside-binding lectin from ovine placenta. The complete amino-acid sequence, obtained by tryptic and chymotryptic digestion, revealed that this carbohydrate-binding protein shares all the absolutely preserved and critical residues found in other members of the mammalian galectin-1 subfamily. Moreover, conformational changes induced by protein interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 4 publications
0
45
0
2
Order By: Relevance
“…Gal-1 is known to define autoimmunity, 70 inflammatory neurodegeneration, 71 cardiac inflammation, 72 and tumor escape. 73 74 and recent data confirm that it is not only expressed by the placenta itself 75 but also in uterine NK cells, 76 tolerogenic DCs, 55 and recent data show its importance when expressed in uterine MCs. 58 Pregnancies of Gal-1-deficient mice were first described as normal as the number of born embryos was apparently unaffected by this mutation.…”
Section: Modulators Of the Immune Responses During Pregnancymentioning
confidence: 71%
“…Gal-1 is known to define autoimmunity, 70 inflammatory neurodegeneration, 71 cardiac inflammation, 72 and tumor escape. 73 74 and recent data confirm that it is not only expressed by the placenta itself 75 but also in uterine NK cells, 76 tolerogenic DCs, 55 and recent data show its importance when expressed in uterine MCs. 58 Pregnancies of Gal-1-deficient mice were first described as normal as the number of born embryos was apparently unaffected by this mutation.…”
Section: Modulators Of the Immune Responses During Pregnancymentioning
confidence: 71%
“…4 Its presence has been localized within the central and peripheral immune compartment in thymic epithelial cells, 5 activated T cells 6,7 and activated macrophages. 8,9 It has also been found in immune privileged sites of the body such as placenta, 10,11 cornea 12 and testis. 13 Recent observations suggest that Gal-1 could play an important role in generating and maintaining central and peripheral immune tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Galectin-1 is also present in sites of immune privilege, such as placenta (Hirabayashi and Kasai, 1988;Iglesias et al, 1998a), cornea (Ogden et al, 1998) and prostate (Allen et al, 1991;Hirabayashi and Kasai, 1993). The presence of this protein in these vulnerable sites might contribute to mantain a state of tolerance by inducing apoptosis of inflammatory and activated T cells that could provoke injury, autoimmune damage or infection.…”
Section: Galectin-1 Expression In Immune Privileged Sites" a Novel Mementioning
confidence: 99%
“…Accordingly, galectin-1 could also be proposed as an alternative regulatory signal to regulate immune privilege. Expression of this protein in first term gestation placenta would prevent inflammatory T cells from harming the fetus (Iglesias et al, 1998a (1995) showed that the T lymphoblastoid cell line MOLT-4 that was unsensitive to FasL-induced apoptosis, was susceptible to galectin-1. In contrast, the T lymphoblastoid cell line CEM, which was sensitive to FasL was resistant to galectin-l-induced apoptosis.…”
Section: Galectin-1 Expression In Immune Privileged Sites" a Novel Mementioning
confidence: 99%
See 1 more Smart Citation